An alternatively spliced region of the human hexabrachion contains a repeat of potential N-glycosylation sites. - Gulcher, J R (1989)
We have cloned and sequenced two cDNA molecules that code for parts of two forms of human hexabrachion. The smaller clone has a sequence that corresponds to the previously published sequence of a cDNA clone coding for a part of chicken hexabrachion [Jones, F. S., Burgoon, M. P., Hoffman, S., Crossin, K. L., Cunningham, B. A. & Edelman, G. M. (1988) Proc. Natl. Acad. Sci. USA 85, 2186-2190]. It has eight consecutive domains similar to the type III homology units from fibronectin, several epidermal growth factor repeats, and a domain similar to the beta and gamma chains of fibrinogen. The larger clone has 5' and 3' ends that are identical to the smaller clone but also has an alternatively spliced 1.9-kilobase internal segment. The unique segment contains remarkable repeats of potential glycosylation sites and an additional seven type III homology units.